Hubungan Antara Kepercayaan Diri dan Konformitas Teman Sebaya Dengan Perilaku Konsumtif pada Remaja Sosial Ekonomi Menengah Ke Bawah - Reynaldi Faisal Ardiansyah; Latifah Nur Ahyani (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to examine the relationship between self-confidence and peer conformity with consumptive behavior among lower-middle socioeconomic adolescents. This study uses a correlational quantitative design with a sample of 200 adolescents aged 12–21 years residing in Jepara Regency. The sampling technique used was quota sampling. The research instruments were Likert scales consisting of a consumptive behavior scale, a self-confidence scale, and a peer conformity scale. Data analysis used multiple linear regression and product-moment correlation. The results showed a highly significant relationship between self-confidence and peer conformity simultaneously with consumptive behavior (Rx12y = 0.660; R² = 0.436; p = 0.000) with an effective contribution of 43.6%. Self-confidence has a significant negative relationship (r = -0.505), while peer conformity has a significant positive relationship (r = 0.627) with consumptive behavior. In conclusion, the lower the self-confidence and the higher the peer conformity, the higher the consumptive behavior in adolescents.